Opportunities for the formation of economic consciousness in the younger generation - Халитова, Мадина; Халитова, Исламия; Атемкулова, Н. (Pedagogy and Psychology, 2022)
Studying economic consciousness, it was noted that in the younger generation it is necessary to consider the possibilities of its formation. It is necessary to search for ways to form the economic consciousness of the younger generation in accordance with the requirements of the time.To assess the level of economic consciousness, the paper defines criteria and indicators of the formation of economic consciousness among the younger generation. At the same time, it is concluded that, on the one hand, a person in the subconscious thinks about his own benefit, and on the other - about compliance with the requirements of society. The individual tries from all sides to think about and compare his actions with the phenomena taking place in society, critically assessing, determines his ideals and goals, plans future activities, which is a necessity at this time. At all times, a person strives for the maximum satisfaction of his needs. In the modern world, certain resources are needed to achieve these goals, which confirms the importance of economic thinking and consciousness.Every member of society needs economic knowledge, skills and practical skills, but they will be effective if they have been consciously mastered. With the development of society, human needs increase and change. Here there is a problem of matching opportunities to needs, which once again confirms the need to acquire basic economic knowledge.But needs and opportunities are constantly changing and economic knowledge is also constantly being updated, which reflects the need for transformation of economic consciousness. The article was prepared within the framework of the IRN grant study AP09259332 - Transformation of the economic consciousness of society in the conditions of the pathology of the economy (on the example of the Republic of Kazakhstan)